N and P fertilization enhanced carbon decomposition function by shifting microbes towards an r-selected community in meadow grassland soils - Zhihui Wang (Elsevier, 2021)
Applications of mineral nitrogen (N) and phosphorus (P) fertilizer to grasslands become more frequently in recent decade, aiming to improve the grass production. Nonetheless, the ecological impacts of N and P fertilizer on ecosystem components, especially the belowground soil microbes, are not well acknowledged in grasslands ecosystem. We investigated the responses of plant traits, soil properties, bacterial community composition and potential functions to 5-year N and P fertilization in a mid-high latitude meadow grassland in Inner Mongolia, China. Bacterial species richness and diversity significantly (P < 0.05) decreased under combined N and P fertilization treatment. The overall bacterial community composition was significantly (PERMANOVA, P < 0.05) changed by N and P fertilization. In specific, N and P fertilization increased the relative abundance of the nominated r-strategists (copiotrophs), such as Actiobacteria, Candidatus Saccharibacteria, and Firmicutes; whereas reduced the relative abundance of the putative K-strategists (oligotrophs), including Acidobacteria, Gammaproteobacteria, and Deltaproteobacteria. As a consequence, the ratio of r-strategists to K strategists (r/K ratio) increased under nutrients addition. The shifts towards an r-selected community were further verified by the increased averaged rRNA operon copy number (rrn) of bacterial communigy. Soil N cycling process was inhibited by N fertilization, whereas soil C metabolizing function was accelerated by N and P fertilization. It implies that application of N and P fertilization will increase the risk of C loss in this region. The present study deepens our knowledge on the impacts of N and P fertilization on soil biotic and abiotic parameters in an organic-carbon-rich meadow grassland ecosystem. It provides a reference for designing a sustainable grassland management that can balance the grass yield and environment protection.